Anthropometric profile of high school students - Maesaroh, Dea; Nurbait, Syifa; Bastian, Risa Herdiyana (Universitas Tanjungpura, 2024)
Anthropometry can be defined as the science of measuring the human body. Because anthropometry is very important for improving academic performance, the current problem addressed by this study is the decline in academic performance due to the lack of anthropometric data collected in schools. Physical education teachers find it difficult to select prospective athletes or high-achieving students, so the researchers helped the school by collecting data on 11th grade students to conduct anthropometric tests. The purpose of this study was to provide an overview of the physical and nutritional conditions of the students and to serve as a reference for improving the quality of athletes. The method used in this study was quantitative descriptive, which only describes or explains the results of anthropometric measurements on students. The instruments used were the DBON 8 criteria measurement test (weight, height, leg length, palm length, foot length, arm span, hand span, sitting height), and documentation. The population was 11th grade students at SMA Negeri 3 Kota Cirebon. The sample used was purposive sampling. Based on the results of research analysis and data processing using descriptive statistics for body measurements of 30 students, it was found that class 11 A had the criteria for athletes, as seen from the minimum, maximum, mean, and standard deviation values of the eight types of measurements. Therefore, it can be concluded that the anthropometric measurements of students in class 11 A at SMA Negeri 3 Kota Cirebon show that the 8 types of anthropometric measurements determined by KEMENPORA indicate that the students have ideal body weight and height. and measurements such as hand span, arm span, hand length, foot length, sitting height, and leg length, 85% of students in class 11 have athletic bodies.